The Relationship between Parent's Attention and Learning Motivation of Elementary School Students during the Pandemic Period - Dearda Yulia Mayona; Dwi Purbowati; Amining Rahmasiwi (Faculty of Tarbiyah, UIN Raden Mas Said Surakarta, 2022)
Parents' attention is important to increase students' motivation in learning, especially in difficult conditions, such as during the Covid-19 pandemic. The aims of this study were (1) to find out the level of student motivation during a pandemic in class five, (2) to find out the relationship between parental attention and student learning motivation during a pandemic at 5th-grade Muhammadiyah Gonilan Sukoharjo Islamic Elementary School in 2020/2021. This study uses a quantitative correlational method. This study's population consisted of all Muhammadiyah Gonilan Islamic Elementary School students in 5th grade. The research sample consisted of 50 students of all 5th grades, which was determined through a total sampling technique. Data collection techniques using questionnaires and interviews. The data obtained is then tested through a prerequisite test, namely the normality and linearity tests. Test the hypothesis using the Spearman Rank correlation formula. The results showed that: (1) student learning motivation during the pandemic was in the moderate category, (2) parental attention was in the moderate category, (3) the results of the hypothesis test showed that there was a relationship between parental attention and student learning motivation during the 5th-grade Muhammadiyah Gonilan Sukoharjo Islamic Elementary School in 2020/2021 academic year.